Pemahaman Hukum terhadap Kejahatan Pemilihan Umum Kepala Daerah yang Dilakukan oleh Aparatur Sipil Negara - Badaru, Baharuddin (Universitas Ekasakti, 2023)
This study aims to know and analyze the types of criminal acts that can be committed by the state civil apparatus (ASN) in the implementation of regional elections and know and analyze the legal settlement of regional head election crimes carried out by the state civil apparatus. The research method used by the author in this case is the normative juridical method. The results showed that the types of criminal acts committed by the state civil apparatus are contained in articles 488-554 of Law Number 7 of 2017, legal settlement of election crimes committed by the state civil apparatus, if the perpetrators of election crimes meet the elements of guilt, then in this case the actions of the perpetrators contain elements of guilt, then the subject of the law must be criminally responsible for mistakes committed in election acts based on Election criminal provisions regulated in Law No. 7 of 2017 are in the flow of handling election criminal violations.